O uczuciach i emocjach na poważnie (nie tylko dla nauczycieli etyki) - Nowak, Ewa (Wydawnictwo Naukowe Instytutu Filozofii, 2012)
In this chapter I focus on the relevance of moral emotions in our „perception of something as moral issue” as well as „in the application of moral norms, but also in their grounding...”. Referring to the statements of philosophy (from Aristotle to Habermas) and developmental psychology (from Piaget to Ekman) I highlight that affectivity needs to be already promoted in the early education. There is a lack of the professional emotional education in the Polish schooling system. Finally I propose a simple training for both teachers and students, in order to strength their skills of understanding facial emotional expressions of others. Mutual respect, trust, and better communicational relationships in the classroom will follow, and, last but not least, the learning processes in pupils will be facilitated too.
Taking feelings and emotions seriously
Keywords: affectivity & ethics; emotional skills; moral sensorium; emotional education; respect for emotions; emotional self-control